Analisis Rasio Keuangan Terhadap Kinerja Keuangan PT Waskita Beton Precast Tbk Periode 2017-2021 (Lembaga Pengembangan Kinerja Dosen, 2023)
Financial performance in the company is needed because it is to find out the goals that have been achieved and evaluate the level of success of the company. Financial performance appraisal is a way to meet the needs of users of financial statements in achieving the targets that have been set which are used in making management decisions related to the effectiveness of the use of equity and the efficiency of company activities. This study analyzes the financial ratios on the financial performance of the company PT Waskiton Beton Precast Tbk for the 2017-2021 period and is analyzed by SPSS 25. The sample used in this study is data from the financial statements of the company PT Waskita Beton Precast Tbk published in the last 5 years from 2017 to 2021 with 50 data. This study uses a regression model equation analysis tool. The results showed that (1) the solvency ratio, activity ratio, profitability ratio to financial performance partially had a positive and significant impact. (2) the liquidity ratio to financial performance partially does not have a significant impact, because financial performance is not always influenced by the good or the negative value of liquidity. Although the company's ability to pay its short-term debt increases, it does not mean that investors will respond well.